From Glass to Glaze in al-Andalus: Local Invention and Technological Transfer. (February 2022) - Salinas, Elena; De Juan, Jorge; Piñero, Juan M.; Casal, M. Teresa; Schibille, Nadine; Pradell, Trinitat
Abstract : It has long been assumed that lead glazing technology preceded glassmaking in the Western world and that the technological transfer was from glazes to glass. Here, we present new evidence for the reverse, the indigenous innovation of glassmaking and its transfer to glazes in early Islamic al-Andalus (Spain). Compositional analyses show that Islamic lead glazes from Córdoba are intimately related to a distinct type of high-lead glass, suggesting a connection between the two technologies. The archaeological remains from a pottery workshop indicate that the glazing process initially involved the production of a lead glass and is not linked to earlier Roman or other contemporary glazing technologies. The data also demonstrate that the potters not only used the same materials and techniques but borrowed stylistic and decorative models from glassmaking.